Wiley Encyclopedia of Management 2015
DOI: 10.1002/9781118785317.weom130034
|View full text |Cite
|
Sign up to set email alerts
|

The Front End of Innovation in Large Established Firms

Abstract: Innovation in large established firms may be broadly divided into three areas: the front end of innovation (also known as fuzzy front end or predevelopment), the new‐product development process, and commercialization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The first (early) stage of product design (PD) process is full of uncertainties and poorly formalized. This is the fuzzy front end (FFE) of PD process, where a concept of product and its feature set are determined and validated (Kim and Wilemon, 2002; Koen et al , 2014; Pereira et al , 2017). Digital technologies and modern social / network infrastructures support knowledge spillovers, create new opportunities and challenges for entrepreneurs in collaboration with external partners (users, customers, suppliers, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The first (early) stage of product design (PD) process is full of uncertainties and poorly formalized. This is the fuzzy front end (FFE) of PD process, where a concept of product and its feature set are determined and validated (Kim and Wilemon, 2002; Koen et al , 2014; Pereira et al , 2017). Digital technologies and modern social / network infrastructures support knowledge spillovers, create new opportunities and challenges for entrepreneurs in collaboration with external partners (users, customers, suppliers, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, prior research [37], [38] have indicated a positive correlation between idea creation and company front-end performance [41]. This performance refers to what extent SMEs can use their knowledge and idea creation to acquire a competitive advantage and succeed in innovation initiatives [35], [37], [40]. Therefore:…”
Section: Hypothesis 7: Network Orientations Positively Affect the Ado...mentioning
confidence: 99%
“…Developing ideas based on current market insights, then incorporating those ideas and knowledge into the creation of new goods and services in innovation projects is one of the fundamental premises of implementing an open innovation model into organizations [20], [35]. Additionally, prior research [37], [38] have indicated a positive correlation between idea creation and company front-end performance [41]. This performance refers to what extent SMEs can use their knowledge and idea creation to acquire a competitive advantage and succeed in innovation initiatives [35], [37], [40].…”
Section: Hypothesis 7: Network Orientations Positively Affect the Ado...mentioning
confidence: 99%
“…The success of innovation and, thus, access to credit for new and small firms in developing countries depends upon FEI. 1 Because of the central role small firms play in economic development, the relationship between FEI and small firm access to credit has consequences for income inequality (Banerjee & Newman, 1993 ; Levine, 2004 ; Koen et al, 2014 ). This incidence suggests that the few entrepreneurs, who have access to credit in emerging markets, have been able to acquire higher incomes over time, with FEI.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental nature of FEI enables the risks and uncertainty associated with an invention/product, to be cleared, before entering the innovation phase. The innovation phase is a continuation of FEI, but with less risk and uncertainty, with access to credit, fully evolved organizational competencies and information, but on a much larger scale (Jovanovic, 1982 ; Kazanjian, 1988 ; Koen et al, 2014 ; Pereira et al, 2017 ).…”
mentioning
confidence: 99%